Malaysia : Publication of Financial Sector Assessment Program Documentation-Detailed Assessment of Observance of Insurance Core Principles. (IMF Staff Country Reports; Country Report, 2013)
This report is an analysis of the insurance core principles of Malaysia. This assessment gives a clear understanding of the regulatory and supervisory framework of the insurance sector of Malaysia. Bank Negara Malaysia (BNM) is the best insurance regulator in this region. Six percent of the financial sector accounts for the insurance sector. The assessment did not reveal any current potential sources of significant risk to the Malaysian financial stability from its insurance industry. The Executive Board expects further enhancement for an effective insurance sector.